An Economic and Political Consequences of Open Remittance Policy: A Critical Literature Review - Abdul Razak Nasution (SEAN Institute, 2023)
In this paper discussed of migration crises in recent decades, scholars have begun to study the effects of international mobility of labours for receiving countries, largely debating whether migrants bring positive or negative economic consequences and whether migrants possess non-material. More than 75 percent of these flows were directed towards low- and middle- income countries. India, China and Mexico were the largest recipient countries, gaining USD 78.6, 67.4, and 35.7 billion, respectively. In terms of GDP, Tonga, Kyrgyz Republic and Tajikistan were the most beneficiaries of financial remittance inflows as it accounts for 35.2, 33.6, and 31 percent of their GDP, respectively. With positive economic trends on remittance-sending countries forecasted, the Bank predicted financial remittance flows to low- and middle- income countries would reach USD 550 billion in 2019, becoming their largest source of external financings for the first time in more than three decades. It is also important to note that actual financial remittance flows are believed to be even larger than the amount estimated by the Bank as remittance flow is assumed to be underreported because migrants may also use informal channels to send remittances.